Analogies végétales dans la connaissance de la vie de l'Antiquité à l'Âge classique - Carvallo, Sarah (Sciences : concepts et problèmes, 2023)
Why and how do doctors use plants to understand and cure the human body? From the plant to the cosmos via the human body, doctors and philosophers conceive in an analogical way human and vegetative seeds, generation, nutrition, circulation, growth and thus bring together things and beings that today may seem us more foreign to each other. The investigation conducted through European medical, botanical, agricultural or philosophical texts from Antiquity to early modernity identifies the uses of plant analogies to say, think, see and care for the human body. The vegetal prism thus makes visible the intuition of a community of elementary processes between different types of living things.